Legalitas Hukum Islam dalam Sistem Peradilan Indonesia - Muhammad Habibi (Media Syari'ah, 2021)
AbstractThis article will explain the legality of Islamic law in the justice system in Indonesia. The importance of this topic to be discussed is because judicial institutions in Indonesia are formed as a result of their multiple historical developments. It was said that because until now in the Unitary State of the Republic of Indonesia, several legal systems had various features, structures, and characteristics, namely; the Islamic legal system, customary law system, and Western legal system. The problem that he explains is related to the legality of Islamic law in the judicial system in Indonesia. To answer the questions above, this article uses a qualitative research method with a library research model as a data collection method. The search results found that there are several regulations that have been legalized so that they become positive laws in Indonesia, namely: 1) the 1945 Constitution; 2) Law Number 17 of 1999 concerning the Implementation of Hajj; 3) Law Number 36 of 1999 concerning Management of Zakat; 4) Law Number 41 of 2004 concerning Waqf; 5) Law Number 44 of 1999 concerning the Implementation of the Specialties of the Aceh Region; 6) Law No. 3 of 2006 concerning Amendments to Law No. 7 of 1989 concerning Religious Courts; 7) Law Number 1 of 1974 concerning Marriage.Abstrak: Artikel ini menjelaskan tentang legalitas hukum Islam dalam sistem peradilan di Indonesia. Pentingnya topik ini untuk dibahas karena, lembaga peradilan di Indonesia terbentuk akibat dari perkembangan sejarahnya yang bersifat majemuk. Dikatakan demikian, karena sampai saat ini di Negara Kesatuan Republik Indonesia berlaku beberapa sistem hukum yang memiliki corak, susunan dan karakteristik yang beragam, yaitu; sistem hukum Islam, sistem hukum Adat, dan sistem hukum Barat. Permasalahan yang jelaskan berkaitan dengan legalitas hukum Islam dalam sistem peradilan di Indonesia. Untuk menjawab pertanyaan di atas, artikel ini menggunakan metode penelitian kualitatif dengan model library reseach sebagai metode pengumpulan data. Hasil penelusuran ditemukan bahwa ada beberapa aturan yang telah dilegalisir sehingga menjadi hukum positif di Indonesia, yaitu: 1) Undang-Undang Dasar tahun 1945; 2) Undang-Undang Nomor 17 tahun 1999 tentang Penyelenggaraan Ibadah Haji; 3) Undang-Undang Nomor 36 tahun 1999 tentang Pengelolaan Zakat; 4) Undang-Undang Nomor 41 Tahun 2004 tentang Wakaf; 5) Undang-Undang Nomor 44 tahun 1999 tentang Penyelenggaraan Keistimewaan Daerah Aceh; 6) Undang-Undang Nomor03 Tahun 2006 tentang Perubahan atas Undang-Undang Nomor 7 tahun 1989 tentang Peradilan Agama; 7) Undang-Undang Nomor 01 tahun 1974 tentang Perkawinan.